MUHAMMADIYAH DAN GERAKAN KESEHATAN BERKEMAJUAN - Em Sutrisna (Universitas Muhammadiyah Surakarta, 2015)
Muhammadiyah has contributed greatly to the maintenance of public health. Up to 2015 Data of muhamaditah hospitals/ KBIA / BP / maternity hospital owned by Muhammadiyah reached 457. The number of Muhammadiyah hospitals is because of the hard work MPKU in running programs above. But the number of hospitals and clinics does not necessarily bring health implications of muhammadiyah citizens. Most people have not seen a real contribution of Muhammadiyah (Muhammadiyah hospital).Muhammadiyah Hospital as one of the Muhammadiyah Health Charity expected to be more oriented to charity without forgetting their business, so residents can take muhammadiyah real benefit in health of the existence of the hospital, and the future expected Muhammadiyah became a pioneer in e-hospital, health tourism and travel medicine to face global challenges of health as part of the da’wah of Muhammadiyah in health.